1984
DOI: 10.1902/jop.1984.55.8.486
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Prophy‐Jet® as an Instrument for Routine Removal of Tooth Stain and Plaque

Abstract: The Prophy-Jet was evaluated for its effectiveness in removing plaque and stain from teeth and on its effects on the marginal gingiva. Using a randomized split-mouth design, half the mouth was treated with the Prophy-Jet and the contralateral side with a rubber cup and prophylaxis paste. The results indicated that the Prophy-Jet removes tooth plaque and stain as well as the rubber cup and prophylaxis paste method, and does so in less time. It was also found that there was some immediate soft tissue trauma foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
115
0
17

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(135 citation statements)
references
References 3 publications
3
115
0
17
Order By: Relevance
“…Especially in the field of prosthetic dentistry, the control and removal of dental plaque deposits and subsequent polishing seems to be essential for the longevity of restorations. Air-polishing devices (APDs) have become an effective tool for plaque control and are applied routinely in professional dental cleaning [10][11][12][13][14] . However, adverse effects of APDs on dental restorative materials have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the field of prosthetic dentistry, the control and removal of dental plaque deposits and subsequent polishing seems to be essential for the longevity of restorations. Air-polishing devices (APDs) have become an effective tool for plaque control and are applied routinely in professional dental cleaning [10][11][12][13][14] . However, adverse effects of APDs on dental restorative materials have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Until 1980, the dentists performed dental prophylaxis using rubber cups and brushes with an abrasive low speed motor. With the emergence of a new method consisting of a spray comprised of powder sodium bicarbonate, water and air, dental prophylaxis became more rapid and efficient [1][2][3] . Sodium bicarbonate is a nontoxic, water soluble abrasive that is considered ideal for intra-oral use.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium bicarbonate can so lead to substantial erosion or blunting of restorative materials, with the exception of ceramics, which seem to experience a less significant loss of substance 9,[12][13][14] . Still, there is epithelial erosion and exposure of underlying connective tissue in the soft tissues around the tooth 3,[15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…2 Air-powder polishing systems use air, water, and sodium bicarbonate to deliver a controlled stream that propels specially processed sodium bicarbonate particles to the tooth surface. [3][4][5] It has been demonstrated that this increasingly popular technique requires less time and less physical exertion by the operator than polishing with a rubber cup and prophylaxis paste.…”
mentioning
confidence: 99%
“…In addition, no heat is generated with this type of system. 2 Studies of the air-powder polishing method have examined its efficacy in stain removal 2 and its effects on soft tissue, 2,6-12 hard tissue, 5,13,14 and restorative materials. 3,15,16 William et al 15 found that air-powder polishing treatment imparted a nonuniformly roughened surface to enamel.…”
mentioning
confidence: 99%